Decoupling of global metabolic flux and proteome partitioning in bacteria - Ryan Thiermann; Jin Yang; Aniket Zodage; Fukang She; Danny K. Fung; Taylor Rytlewski; Farshad Abdollah-Nia; Fangzhou Xiao; John T. Sauls; Sarah Cox; Zulfar Ghulam-Jelani; Victoria Castillo; et al. (Science, 2026)
Bacteria regulate homeostatic growth by adjusting proteome composition. In Escherichia coli , this coordination is mediated by guanosine tetraphosphate and pentaphosphate, collectively termed (p)ppGpp, which couple amino acid supply with ribsosome production. We identified a distinct architecture in Bacillus subtilis , in which guanosine triphosphate (GTP), not (p)ppGpp, controls proteome allocation. Translational inhibition resulted in GTP depletion and suppressed amino acid biosynthesis through feedback inhibition without altering ribosome abundance, establishing a regulated decoupling between total amino acid flux and proteome composition, with flux deviating from proteome-based predictions. By artificially adjusting GTP concentrations, we recoupled flux and proteome, restoring growth to maximal amounts. The regulated suboptimality enables a trade-off to balance growth and stress resilience. Similar GTP-based strategies were present in other Firmicute species, indicating possible evolutionary conservation. Proteome composition and metabolic flux have distinct regulatory layers in some bacteria.